2014
DOI: 10.1002/2013jd021294
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of ozone in the tropical lower stratosphere: Southern tropics are different from northern tropics

Abstract: We examine the seasonal behavior of ozone by using measurements from various instruments including ozonesondes, Aura Microwave Limb Sounder, and Stratospheric Aerosol and Gas Experiment II. We find that the magnitude of the annual variation in ozone, as a percentage of the mean ozone, exhibits a maximum at or slightly above the tropical tropopause. The maximum is larger in the northern tropics than in the southern tropics, and the annual maximum of ozone in the southern tropics occurs 2 months later than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 35 publications
8
50
0
Order By: Relevance
“…The maximum radiative warming is found in October, ranging from 2.3 K at 208S to 1.2 K at 108S. This result is consistent with Stolarski et al (2014), who emphasized that the tropical lower-stratosphere ozone seasonal cycle is smaller in the SH than the NH, and SH seasonal cycle lags the NH cycle by 1-2 months (cf. Figs.…”
Section: B Sensitivity Experiments and Latitudinal Variabilitysupporting
confidence: 89%
See 4 more Smart Citations
“…The maximum radiative warming is found in October, ranging from 2.3 K at 208S to 1.2 K at 108S. This result is consistent with Stolarski et al (2014), who emphasized that the tropical lower-stratosphere ozone seasonal cycle is smaller in the SH than the NH, and SH seasonal cycle lags the NH cycle by 1-2 months (cf. Figs.…”
Section: B Sensitivity Experiments and Latitudinal Variabilitysupporting
confidence: 89%
“…A recent study by Stolarski et al (2014) found that asymmetrical upwelling and mixing between the Northern and Southern Hemispheres (NH and SH, respectively) leads to a larger amplitude ozone seasonal cycle in the NH (08-208N) than the SH (208S-08). In particular, lowerstratospheric upwelling and horizontal mixing impacts on ozone are in phase and additive in the NH tropics, whereas they are out of phase in the SH tropics.…”
Section: A Observationsmentioning
confidence: 99%
See 3 more Smart Citations